Unearthing the Academic Time Capsule: Delving into the Evolution of Science Education Among Indonesian Students - Ikmanda Nugraha (Journal of Science Learning, 2023)
The Indonesian education system, in general, still has many challenges in learning science. The results of the 2018 PISA survey put Indonesia in 74th place, which is sixth from the bottom. Indonesian students' reading ability, with a score of 371, is in the 74th position; Mathematics, with 379, is in the 73rd position; and Science, with a score of 396, is in the 71st position. This situation is intriguing to explore how history influences the education system's current conditions, especially in science learning. The article will explore the effect of changes in the education system on science learning in Indonesia. Exploration of science learning will start from the education system before the independence of Indonesia to the current education system. Using a historical approach, and this article concludes that political power influences change in the ideological orientation of the system and the direction of education, especially in education policy, curriculum changes, and learning activities. This change in situation plays a huge role in determining the achievements of current science learning and achievements.